Perception of german vowels by bilingual portuguese-german returnees: a case of phonological attrition? - Flores, Cristina (2011)
This study investigates the perception of German vowels by a group of eight Portuguese adolescents and young adults who were raised bilingually in Germany and returned to Portugal in early childhood (between the ages of 5 and 10 years). All the participants reported that they never use German in Portugal and that they are unable to formulate accurate sentences in that language. Our aim was to test whether their perceptual ability to discriminate German sounds had undergone attrition or remained invulnerable to the lack of language use. Unlike German vowels, Portuguese vowels are not distinctive in duration and the Portuguese inventory does not contain the rounded vowels /y/ and /y:/ or the lax vowels /i/ and /~/. Thus, we tested the participants’ perceptual ability to discriminate vowels in terms of (i) duration, in the contrast /a-a:/; (ii) quality+duration, in the contrasts /i-i:/ and /~-u:/; and (iii) quality in the contrasts /i-y/, /~-Y/, /i:-y:/ and /u:-y:/ by means of a categorical discrimination test. The results reveal that the returnees were able to make vowel duration and quality perceptual distinctions in the attrited language. This indicates that their ability to discriminate German sounds seems to remain stable.